The equation 53x+113=−43

is solved as follows. Fill in the correct numbers to complete the solution.

1 answer

To solve the equation \( 53x + 113 = -43 \), follow these steps:

  1. Subtract 113 from both sides:

    \[ 53x + 113 - 113 = -43 - 113 \]

    This simplifies to:

    \[ 53x = -156 \]

  2. Divide both sides by 53:

    \[ x = \frac{-156}{53} \]

Now, calculating that division gives:

\[ x = -\frac{156}{53} \approx -2.943396226415094 \]

Thus, the final solution to the equation \( 53x + 113 = -43 \) is:

\[ x \approx -2.94 \]

So, the complete solution filled in is:

  • Subtract 113
  • Divide by 53